PENGARUH EARNING PER SHARE, DEBT TO ASSET RATIO, DEBT TO EQUITY RATIO DAN RETURN ON EQUITY TERHADAP PRICE TO BOOK VALUE - Furniawan Furniawan (The Asia Pacific Journal Of Management Studies, 2019)
This research is motivated by the problem of price to book value which is one of the ratios in assessing the sustainability of the company with the aim to find out how independent variables such as earnings per share, debt to asset ratio, debt to equity ratio and return on equity affect the price to book value LQ 45 index companies listed on the Indonesia Stock Exchange.The method used in this study is a quantitative research method with a descriptive approach, while the population in this study are all companies incorporated in the LQ 45 index with a sample of 40 companies after adjusting for sampling criteria.Together the earning per share variable, debt to asset ratio, debt to equity ratio and return on equity ratio to price to book value have Asymp values. Sig. (2-tailed) of 0.881 shows the results (0.881> 0.05) meaning that the data is in Normal distribution. Based on testing the correlation between the variables X and Y simultaneously obtained the r value of 0.974. Contributions made by the four independent variables to the dependent variable obtained R2 by 95% while the remaining 5% is influenced by other factors. Based on the results of simultaneous testing using the F test produces a Fcount value of 164.666 with a significance value of 0,000 where 0,000 <0.05 means the results are significant. While the Ftable value of 2.63 means that Fcount> Ftable, then Ho is rejected. This means that simultaneously there is a significant influence between earnings per share, debt to asset ratio, debt to equity ratio and return on equity to the price to book value ratio.